2011
DOI: 10.4049/jimmunol.1100024
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary Collectins Play Distinct Roles in Host Defense against Mycobacterium avium

Abstract: Pulmonary collectins, surfactant protein A (SP-A) and surfactant protein D (SP-D), play important roles in the innate immunity of the lung. Mycobacterium avium is one of the well-known opportunistic pathogens that can replicate within macrophages. We examined the effects of pulmonary collectins in host defense against M. avium infection achieved via direct interaction between bacteria and collectins. Although both pulmonary collectins bound to M. avium in a Ca2+-dependent manner, these collectins revealed dist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(26 citation statements)
references
References 46 publications
(56 reference statements)
1
25
0
Order By: Relevance
“…3,4 For example, SP-D prevents dissemination of infectious microbes by their biological activities including agglutination and growth inhibition. [5][6][7] SP-D also promotes clearance of microbes by enhancing phagocytosis in macrophages. 8,9 In addition, SP-D interacts with the other pattern-recognition molecules including Toll-like receptors (TLRs) and TLR-associated molecules CD14 and MD-2, and regulates inflammatory responses.…”
Section: Introductionmentioning
confidence: 99%
“…3,4 For example, SP-D prevents dissemination of infectious microbes by their biological activities including agglutination and growth inhibition. [5][6][7] SP-D also promotes clearance of microbes by enhancing phagocytosis in macrophages. 8,9 In addition, SP-D interacts with the other pattern-recognition molecules including Toll-like receptors (TLRs) and TLR-associated molecules CD14 and MD-2, and regulates inflammatory responses.…”
Section: Introductionmentioning
confidence: 99%
“…Analysis of the crystal structure of SP-A reveals an extensive hydrophobic surface, which contributes to differences in binding specificity observed between this protein and SP-D [26]. When binding to Mycobacterium avium , SP-A binds lipid ligand on M. avium containing no saccharide, while SP-D binds mannose-rich glycolipid, lipoarabinomannan [27]. These findings suggest that SP-A tends to bind more to hydrophobic ligand than SP-D.…”
Section: Direct Actions Of Pulmonary Collectins On Microbesmentioning
confidence: 99%
“…These data infer that pulmonary collectins inhibit the growth of M . avium by forming a physical barrier around the bacterial surface to restrict nutrient uptake [27]. …”
Section: Direct Actions Of Pulmonary Collectins On Microbesmentioning
confidence: 99%
See 1 more Smart Citation
“…A previous study has shown that O4-specific polysaccharides from E. coli O4:K6 are composed of D-glucose, L-rhamnose, 2-acetamido-2,6-dideoxy-L-galactose, and 2-acetamido-2-deoxy-D-glucose (36). On the other hand, SP-D binds lipoarabinomannan on M. tuberculosis and M. avium (37)(38)(39) and lipids on Mycoplasma pneumonia (40). O-antigen, a glycolipid, or a lipid on UPEC could be a candidate for an SP-D ligand.…”
Section: Discussionmentioning
confidence: 99%